Analisis Kebutuhan Korban Bencana Alam Gunung Meletus dan Upaya Penanggulangannya - Chulaifah Chulaifah (Balai Besar Litbang Pelayanan Kesejahteraan Sosial, 2013)
Geographically, Indonesia is located at a cross section between Asia and Australia continents, and between Indonesia and Pasific ocean. The position is prone zone of natural disaster. Natural disaster happens because of several natural happening, such as erthquake, tsunami, flood, drought, hurricane, landslide, and mountain explosion. One of the enormous natural disaster was the Merapi expolsion that happened in 2010. The impact of that expolision was a lost, death, burned properties and animal farming, devastated houses, and left trauma on the victims, even longlive invalid. The research on analysis of Merapi explosion natural disaster victim needs and its preventive effort meant to know the victims need where the disaster happened. The result showed that the victims needs of disaster victims are physical, psychological, ans social. The preventive effort can be devided in three phases, predisaster (socializing the cause of natural disaster and environmental betterment), having disaster (saving lives), rehabilitation and reconstruction (recovering psychological, physical, social and economic condition, development activities). It is recommended that the Ministry of Social Affairs and its related institution should socialize to the communities prone disaster through social information and training program on natural disaster prevention, including pre-disaster, having disaster, and reconstruction and rehabilitation phases. For the communities prone to natural disaster should participate in the program in order to having skill on disaster prevention.